SIGNIFIKANSI STRATEGI PEMBELAJARAN PENDIDIKAN LINGKUNGAN DALAM MEMBENTUK PRILAKU SISWA BERWAWASAN LINGKUNGAN - Abdul Kadir (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2013)
Damage to the environment and natural resources, because of the additional population is notcontrolled, the knowledge and skills necessary having direct applications in everyday life,become a pattern of acts and mindset for handling specific problems faced by the nation.Education of demography and Environment (PKLH) is one response to the problem. PKLH’slearning, especially at the unit level education can be achieved through two approaches,namely the monolithic approach and integrative approach. PKLH learning strategies asprocedures used by educators /teachers in the learning process as a means to achieve thePKLH learning objectives. PKLH‘s Learning strategies has significance to changes studentbehavior who conception about demography and enviroment . The use of learning strategiesPKLH, educators /teachers need to incorporate some learning strategies that allow theongoing of clarification and internalization of values about demography and theenvironment in students.Keywords; PKLH, Strategic Learning, Significance, and Insight Student Population and theEnvironment.